1989
DOI: 10.1111/j.1365-2133.1989.tb01347.x
|View full text |Cite
|
Sign up to set email alerts
|

Human cutaneous mast cells–a study of fixative and staining reactions in normal skin

Abstract: Routinely used formal saline fixation reduces the number of demonstrable mast cells in human skin by up to 30% compared with paired specimens fixed in Carnoys medium. Using metachromatic (toluidene blue), orthochromatic (alcian blue/safranin), enzymatic (chloroacetate esterase reaction) and immunofluorescence (berberine and fluorescein conjugated avidin) staining techniques, mast cells were demonstrated and quantified. Alcian blue/safranin and fluorescein-conjugated avidin were both superior to the other stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…Brains were fixed with 4% (wt/vol) paraformaldehyde/0.1% glutaraldehyde. Vibratome sections (50 unm) were stained in 1% (wt/vol) alcian blue and counterstained using 0.5% safranin (16 (wt/vol) 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (Sigma) (17). These brains were cut on a cryostat (30 ,um (21), and administered in 7 pl of avian saline over 7 min at the time of pairing via an indwelling cannula in the lateral ventricle (22).…”
Section: Methodsmentioning
confidence: 99%
“…Brains were fixed with 4% (wt/vol) paraformaldehyde/0.1% glutaraldehyde. Vibratome sections (50 unm) were stained in 1% (wt/vol) alcian blue and counterstained using 0.5% safranin (16 (wt/vol) 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (Sigma) (17). These brains were cut on a cryostat (30 ,um (21), and administered in 7 pl of avian saline over 7 min at the time of pairing via an indwelling cannula in the lateral ventricle (22).…”
Section: Methodsmentioning
confidence: 99%
“…For quantifying mastocytosis within the large intestine, ϳ3 mm of gut was taken from the cecal tip of each animal and fixed in Carnoys fluid (39). This tissue was embedded in wax, sectioned at 5 m, dewaxed, and stained in toluidine blue (BDH) for 24 h. Mastocytosis was assessed as the number of mast cells per 20 crypt units; mast cells were counted in two sections per animal.…”
Section: Micementioning
confidence: 99%
“…The observed loss of metachromatic stain ing with formaldehyde-based fixatives for a popula tion of mast cells has provided important evidence for the heterogeneity of this cell type. Most mast cells are sensitive to formaldehyde fixation in the lung [10], nose [11,12], and intestinal mucosa [13][14][15], whereas skin mast cells are considerably more resistant [12,[16][17][18], There is further anatomical variation in the histochemical properties of these cells within organ structures. In the lung it has been reported that the staining of most mast cells in bronchial epithelium, lamina propria, and parenchyma is abolished by prior formaldehyde fixation, while those in the bron chial submucosa are relatively unaffected [10].…”
Section: Introductionmentioning
confidence: 99%